Assessing the Attitudes of Japanese Junior High School Students towards Course Units of Mathematics: A Focus on Learners with 'No Problem' Feeling about Studying the Subject - Nishikawa, Tomoko; Izuta, Guido (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
This article is concerned with the assessment of feelings that Japanese junior high school students have towards unit learning of mathematics courses. To accomplish this purpose, 616 junior high school students of a typical public school were surveyed regarding their feelings towards these course units and a two-step analysis was carried out. The first part consisted of the tabulation of Likert scale type survey with 5 levels of evaluation from 1 (‘not good at’) through 5 (‘good at’) aimed to evaluate their feelings towards learning mathematics in general as part of their educational activity. Next, we looked only into the students who responded ‘no problem’. As a matter of fact, these respondents accounted for 181 students in all with 44 of them in first year, 75 in second year, and 63 in third year. Now focusing strictly on these students, we performed a correspondence analysis of their feelings towards the course units. The results are discussed in terms of this correspondence analysis, which made it clear that despite the fact that the students do not feel resistance towards learning the subjects of mathematics, they have ‘good at’ and ‘not good at’ feelings towards particular unit learning independent of the gender. In the paper, we discussed these findings in detail.